2013
DOI: 10.1007/s40309-013-0020-7
|View full text |Cite
|
Sign up to set email alerts
|

Social media analytics for future oriented policy making

Abstract: Research indicates that evidence-based policy making is most successful when public administrators refer to diversified information portfolios. With the rising prominence of social media in the last decade, this paper argues that governments can benefit from integrating this publically available, user-generated data through the technique of social media analytics (SMA). There are already several initiatives set up to predict future policy issues, e.g. for the policy fields of crisis mitigation or migrant integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 14 publications
(15 reference statements)
0
26
0
Order By: Relevance
“…Social networks have a significant impact on the performance of governments. For example, as a result of the survey, it has been shown that the impact of social media on the political activity of citizens and political participation is increasingly important (Grubmüller, Götsch, & Krieger, 2013;Kamiloglu & Erdogan, 2014;Park et al, 2016;Rainie et al, 2012). Experts note that social media will help governments to become more transparent by providing citizens with better service and access to information, by opening an active channel with them, and ultimately empowering citizens (Bertot, Jaeger & Grimes, 2010;Khasawneh & Abu-Shanab, 2013;Song & Lee, 2016).…”
Section: Role and Security Issues Of Social Network In E-governmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Social networks have a significant impact on the performance of governments. For example, as a result of the survey, it has been shown that the impact of social media on the political activity of citizens and political participation is increasingly important (Grubmüller, Götsch, & Krieger, 2013;Kamiloglu & Erdogan, 2014;Park et al, 2016;Rainie et al, 2012). Experts note that social media will help governments to become more transparent by providing citizens with better service and access to information, by opening an active channel with them, and ultimately empowering citizens (Bertot, Jaeger & Grimes, 2010;Khasawneh & Abu-Shanab, 2013;Song & Lee, 2016).…”
Section: Role and Security Issues Of Social Network In E-governmentmentioning
confidence: 99%
“…Note that public authorities using social networking analyses pay attention to people as citizens and not as customers and consumers, and expand their activities in publicpolitical areas. Therefore, social media analytics aimed at government purposes requires better judgment for the legal and ethical aspects of various reasons (Grubmüller, Götsch, & Krieger, 2013;Park et al, 2016;Rainie et al, 2012).…”
Section: Role and Security Issues Of Social Network In E-governmentmentioning
confidence: 99%
“…Providing additional opportunities for participation that then get accumulated in simple counting tables or word clouds may fail to satisfy participants that their contribution was valued. Social listening and sentiment analysis is rapidly improving (Grubmüller, Götsch, and Krieger ), but determining what someone means when they use a hashtag promoted by a government consultative process is not a simple counting exercise and will require advances in the analytical skills of conveners (Pak and Paroubek ; Till et al ).…”
Section: Future Agendamentioning
confidence: 99%
“…without considering the participation of potential users at the time of delivering that proposal, and without evaluating their reactions and expectancies beforehand (Acordino, 2013). Social networks, which are based on real-time online participation, have provided the key to shape the aforementioned political alternatives (Grubmüller et al, 2013;Dadashzadeh, 2010) (as in the case of "Podemos" in Spain, the fourth most voted option for the 2014 European Parliament Elections). This is why participatory foresight makes sense, and why participatory, open processes concerning futures research could be seen as the future of foresight right now.…”
Section: Discussionmentioning
confidence: 99%